CREATIVITY OF O. EXTER AS A SOURCE OF COMPOSITION AND ART-GRAPHIC TECHNIQUES FOR THE DEVELOPMENT OF MODERN CLOTHING COLLECTIONS - Давиденко, І. В.; Кокоріна , Г. В.; Чупріна , Н. В.; Гаркін, П. В.; Сельский , Р. М. (Art and Design, 2023)
Purpose: to study the relevance and ways of applying the design approaches of the outstanding artist of the first half of the 20th century, Olexandra Ekster, in modern fashion design. Methodology. Methods of literary-analytical and systematic-historiographical analysis, methods of classification of compositional techniques of form formation were used in the conduct of scientific research. Results. The creative legacy of the outstanding Ukrainian artist and designer O. Ekster is represented, some aspects of her work in the field of fashion graphics and costume composition are highlighted. The contribution of the artist to the development of the avant-garde movement in Ukraine is presented, the logic of the formation of her views on the relationship of form and color in the costume, practical experience of constructive modeling of clothes, interpretation of the traditions of the Ukrainian national costume are explored. The relevance of O. Ekster's work has been proven in view of the current problems of modern design, the works of modern costume designers, specialists in artistic embroidery, accessories and headdresses inspired by the art of the outstanding Ukrainian artist have been analyzed. Scientific novelty. The research results highlight innovative approaches to costume design using the example of O. Ekster's work. The actualization of the experience of historical domestic design in the context of modern problems of clothing design is proven. Practical significance. Examples of the interpretation of the design paradigm of O. Exter in the process of creating modern fashion design samples are presented, which illustrates the wide possibilities of using the results of scientific work in the process of training and practical activities of modern clothing designers.